University service quality measurement model in Peru: Multifactorial validation - Espinoza-Montes, Isac Fernando; Soldevilla-Espinal, Yuzara; Yurivilca-Oscanoa, Martín Romeo (Jurnal Cakrawala Pendidikan, 2025)
The quality of university services plays a fundamental role in improving the student experience and shaping highly competent professionals. In this context, the study aimed to develop and validate a multidimensional model to comprehensively assess university service quality in Peru, a country facing unique educational challenges. Using a quantitative and cross-sectional design, data were collected from 1,170 students across 20 universities through the University Service Quality Scale (CEUS), specifically designed for this research. Exploratory and confirmatory factor analyses identified five key dimensions: Quality of Academic and Support Processes (QuAcSuPr), Curriculum (Cu), Teaching Quality (TeQu), Library Services (LiSe), and Educational Sustainability (EdSu). The results showed robust fit indices (IFI=0.988, CFI=0.988, TLI=0.984, RMSEA=0.040), confirming the model’s validity and applicability. The model provides a practical framework for evaluating and improving university service quality in Peru, while also emphasizing the importance of integrating educational sustainability as a key dimension to prepare socially responsible graduates. Future studies could adapt the model to other contexts and explore its application in modalities such as online learning.